2020
DOI: 10.3390/jcm9092760
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Hematological Markers of Systemic Inflammation (Neutrophil-To-Lymphocyte, Platelet-To-Lymphocyte, Lymphocyte-To-Monocyte Ratios) and Ultrasound Disease Activity Parameters in Patients with Rheumatoid Arthritis

Abstract: Background: An accurate measurement of disease activity is essential for the appropriate management of a patient with rheumatoid arthritis (RA). Hematological markers of systemic inflammation (Neutrophil-to-Lymphocyte (NLR), Platelet-to-Lymphocyte (PLR) and Lymphocyte-to-Monocyte (LMR) ratios) are reported to be novel, sensitive measures of inflammatory response, in addition to conventional markers (erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), Disease Activity Score (DAS28)). The goal of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 21 publications
1
34
1
1
Order By: Relevance
“…High levels of blood biomarkers such as NLR, PLR, and MLR have been reported in certain inflammatory conditions, including various types of infections [ 23 , 25 , 26 ]. Notably, in comparison with previous data from a study that included 500 healthy individuals with a similar background (Hispanic population), whose normal values are as follow: PLR, mean SD 125.4 ± 36.3, median 120; NLR, mean SD 1.80 ± 0.65, median 1.70; and MLR, mean SD 0.23 ± 0.07, median 0.21 [ 24 ], the levels of these three inflammatory markers (NLR, MLR, and PLR) among the hospitalized patients included in this study were considerably higher ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…High levels of blood biomarkers such as NLR, PLR, and MLR have been reported in certain inflammatory conditions, including various types of infections [ 23 , 25 , 26 ]. Notably, in comparison with previous data from a study that included 500 healthy individuals with a similar background (Hispanic population), whose normal values are as follow: PLR, mean SD 125.4 ± 36.3, median 120; NLR, mean SD 1.80 ± 0.65, median 1.70; and MLR, mean SD 0.23 ± 0.07, median 0.21 [ 24 ], the levels of these three inflammatory markers (NLR, MLR, and PLR) among the hospitalized patients included in this study were considerably higher ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in patients with CKD, an array of immune dysfunctions have been documented. This includes and impaired function of T and B lymphocytes and a lower phagocytic activity of neutrophils and macrophages [ 23 , 24 ]. Furthermore, patients with CKD requiring renal replacement therapy, repeated dialysis sessions may expose them to a possible contaminated environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last few years, hematological parameters of systemic inflammation (the Neutrophil-to-Lymphocyte ratio (NLR) and Platelet-to-Lymphocyte ratio (PLR) have come into use. They have been reported to be sensitive measures of inflammation in different fields of medicine: oncology, diabetes, cardiology, nephrology, infectious diseases, and autoimmune rheumatic diseases, including RA [ 7 , 8 , 9 , 10 , 11 ]. Research found that NLR and PLR correlate with different parameters of RA activity (laboratory, clinical, and ultrasound) and may serve as reliable markers of RA systemic activity.…”
Section: Introductionmentioning
confidence: 99%